2015
DOI: 10.1111/jan.12860
|View full text |Cite
|
Sign up to set email alerts
|

Transformational and abusive leadership practices: impacts on novice nurses, quality of care and intention to leave

Abstract: Paying close attention to the leadership practices of nurse managers could prove effective in improving patient care and increasing the retention of new nurses, which is helpful in resolving the nursing shortage. Our results specifically suggest not only that we promote supportive leadership practices (transformational leadership) but, most of all, that we spread the word that abusive leadership creates working conditions that could be detrimental to the practice of nursing at career start.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
144
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 57 publications
(105 reference statements)
10
144
0
11
Order By: Relevance
“…The major themes of restrictive work practice, top down leadership, normalizing the abnormal in team dynamics and ethical concerns, have also been found internationally to be associated with increased RN turnover. [1,4,25,26] In this study, participants reported feeling unappreciated by their employer due to lack of commensurate benefits and pay, with many describing unfairness in the distribution patterns. Feeling unappreciated emanated from perception of lack of the professional development opportunities and poor remuneration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The major themes of restrictive work practice, top down leadership, normalizing the abnormal in team dynamics and ethical concerns, have also been found internationally to be associated with increased RN turnover. [1,4,25,26] In this study, participants reported feeling unappreciated by their employer due to lack of commensurate benefits and pay, with many describing unfairness in the distribution patterns. Feeling unappreciated emanated from perception of lack of the professional development opportunities and poor remuneration.…”
Section: Discussionmentioning
confidence: 99%
“…[24] The findings of this study concur with evidence that threats and intimidation by an authoritarian leader may lead to frustration among nursing staff and eventual turnover. [4,21] Studies have shown that nurses consider autonomy in nursing practice and control over nursing practice essential for the provision of high quality nursing care. [9] Published by Sciedu Press…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations